Magnetic – acoustic biphysical invisible coats for underwater objects - Zhou, Yi (2021)
Magnetic fields and acoustic waves are the two fundamental measures to perceive underwater objects, which, however, have never been simultaneously handled before. In this work, we propose and demonstrate a biphysical submillimeter-thick metamaterial coat that can simultaneously make underwater objects invisible to both magnetic fields and acoustic waves. The conformal coat is a subtle integration of an open-cavity acoustic absorber made of a dissipative acoustic metasurface (AMS) and a bilayer magnetic cloak. Experimentally, a magnetic cloaking effect with a field disturbance ratio of <0.5% is obtained over a broad-frequency range (10–250 kHz), and the compound metamaterial coat can strongly attenuate ultrasonic waves with a near-unity absorptivity. The magnetic subcoat can be freely combined with various AMS layers to achieve a wideband acoustic stealth effect for different spectral regimes. This work may open up a new way to build multifunctional devices for various waterborne applications.